Hubungan Pemberian Susu Formula dengan Kejadian Diare pada Balita Usia 0-24 Bulan di Wilayah Kerja Puskesmas Banjarbaru - Fitria Aningsih; Agus Rahmadi; Lusiana Lusiana; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2013)
Health is one aspect of social life, quality of life, workforce productivity, morbidity and high mortality in infants and children, the decreasing physical work and mental development is impaired is a direct or indirect result of the health problems of children. This study aims to determine how related event giving milk formula with diarrhea in children working in the area health unite Banjarbaru. This research is an analytic cross sectional population is all women having babies aged 0-24 months coming months poly treatment MTBS at health centers Banjarbaru working area. The samples in this study were 68 people. The analysis was conducted perpetually descriptive and statistical examine chi-square test. From the results of this research note that there is a link between formula feeding with the incidence of diarrhea in children in the working area Banjarbaru Health Center. Expected for parents should remember the content of exclusive breastfeeding exclusive breastfeeding is better than formula milk.